Molar loss further exacerbates 2-VO-induced cognitive impairment associated with the activation of p38MAPK/NFκB pathway - Lu, Yunping; Pang, Qian; Wu, Qianqian; Luo, Bin; Tang, Xiaofei; Jiang, Qingsong (Frontiers in Aging Neuroscience, 2022)
Background: Vascular dementia is characterized by reduced cognitive function due to chronic cerebral hypoperfusion and has become a significant public health challenge as the global population ages. Recent studies suggested that molar loss, a common problem among the elderly, may trigger the development of cognitive decline. Our previous study found that the molar loss affected cognitive dysfunction, and the astrocytes in the hippocampus of chronic cerebral ischemia rats were affected, but the underlying mechanism is unclear. Methods: In this study, we established the animal model of molar loss with 2-VO rats and the Morris water maze was used to test the cognitive ability of rats in each group. The damage to neurons was observed via Nissl staining, and neuronal apoptosis was analyzed by terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) assay in the hippocampus of the rats. Quantitative Real-Time PCR and immunohistochemistry and histology (IHC) were used to detect the expression of p38MAPK, NFκB, caspase 3, and iNOS in the hippocampus. The astrocytes were detected by IHC and Immunofluorescence analysis for GFAP. Results: The Morris water maze test showed that the molar loss aggravated spatial memory learning ability with chronic cerebral ischemia decreased in the rats. The neuronal damage and more apoptotic cells were observed in the hippocampus of 2-VO rats. After molar loss, the mRNA and protein expression of iNOS, p38MAPK, NFκB, and caspase3 were further upregulated in 2-VO rats. Molar loss upregulated GFAP expression, and the p38MAPK positive cells were labeled with the astrocyte marker GFAP. Conclusion: Molar loss can aggravate cognitive impairment in 2-VO rats to a certain extent. The mechanism of molars loss exacerbating the cognitive decline in 2-VO rats may be associated with the activation of the p38MAPK-NFκB-caspase3 signaling pathway, which induces neuronal apoptosis.